CLINICAL AND EPIDEMIOLOGIC FEATURES OF CARIOUS LESIONS OF PERMANENT TEETH IN CHILDREN WHO WERE INTERNALLY DISPLACED AS A RESULT OF WAR IN UKRAINE - Bandrivsky, Yurii; Patskan, Liudmyla; Vydoinyk, Oksana; Kuchyrka, Lesia; Zmarko, Iuliya (Eastern Ukrainian Medical Journal, 2025)
The aim of the study: To assess the prevalence and intensity of dental caries in permanent teeth and to determine the characteristics of its course in children who have undergone forced displacement due to military conflict.Materials and methods. The study was conducted on the basis of the Department of Pediatric Dentistry, I. Horbachevsky Ternopil National Medical University of the Ministry of Health of Ukraine. The study included 160 children aged between 7 and 12 years (the period of the alternating occlusion), divided into two groups: the main group – 80 children who had been displaced to the territory of the Ternopil region as a result of the war in Ukraine; and the comparison group – 80 children who had lived in the Ternopil region since birth. To assess the dental status of the study participants, international standards for the diagnosis of caries were used, namely: the prevalence of caries (determined as a percentage) and the intensity of caries, which was assessed using the DMFT+dft index. The level of activity of the caries process was determined according to the methodology proposed by N.I. Smolyar and N.L. Chuchray (2015).Results. As a result of the study, a critically high prevalence of caries in permanent teeth was objectified in children aged 7–12 years in both study groups: 88,75±5,36 % in the main group and 86.25±5.53% in the comparison group, which corresponds to a mass defeat of caries according to the WHO classification. The intensity of the caries process in the main group (children forced to move) was higher – DMFT+dft = 5.1±0.4, compared to the comparison group – DMFT+dft = 4.2±0.5, indicating the negative impact of stress factors, lifestyle changes and limited access to dental care. It was found that the children in the main group had a subcompensated form of dental caries (46.48±5.92%), whereas the children in the comparison group had a compensated course of the carious process (47.83±6.01%), which could be due to the different mineralisation potential of the oral fluid. In the children of the main group, the decompensated form of this pathology was diagnosed most frequently (53.85±9.78%) in the initial caries of permanent teeth, which may indicate the exhaustion of the adaptive mechanisms of remineralisation of hard dental tissues. The analysis of the localisation of the carious lesions showed the highest prevalence of initial caries on the vestibular surfaces of the maxillary incisors (43.75±5.55% of cases in the main group and 38.75±5.45% of cases in the comparison group), which is consistent with peculiarities of washing the tooth surface with oral fluid.Conclusions. Thus, the study found that the dental status of children forcibly relocated due to military action was characterized by a higher prevalence and intensity of caries, a subcompensated form of caries accompanied by a predominance of affected maxillary incisors, and a greater need for caries treatment compared to children living in relatively stable regions.